El derecho, la ciudad y el libre mercado en el Perú entre 1990-2023 - Calderón Cockburn, Julio (2025)
The article carries out a review of the laws issued in Peru between 1990 and 2023 that have effects on cities. Legislation from civil, urban, and environmental law is considered, affirming that the law is not uniform, but rather that within it, there are various orientations regarding private ownership of land, urban planning, informality, among other aspects. Based on a bibliographic review, the article concludes that there is a subordination of diffuse collective rights to private property rights, although changes are observed in this regard.